Perbandingan Hasil Pemeriksaan Tuberkulosis Metode GeneXpert dan Ziehl-Neelsen di Rumah Sakit X Yogyakarta - Andini Bilindade; Wiwit Probowati; Widaninggar Rahma Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. The tuberculosis (TB) detection methods used are the GeneXpert method and the Ziehl-Neelsen method. GeneXpert identifies the rpoB hotspot gene bacteria in Mycobacterium tuberculosis by analyzing deoxyribonucleic acid (DNA), while the TB detection method with Ziehl-Neelsen staining is a microscopic examination used to detect acid-fast bacilli (AFB), namely Mycobacterium tuberculosis bacteria. The purpose of this study was to determine the sensitivity, specificity and positive predictive value of the nucleic acid amplification test (GeneXpert) using sputum samples in patients with suspected pulmonary tuberculosis and compare it with microscopic examination (Ziehl-Neelsen staining) of Acid-Fast Bacilli (AFB). The method used is simple random sampling which explains the comparison between the variables of the GeneXpert and Ziehl-Neelsen examination results in pulmonary tuberculosis patients using a cross-sectional approach, namely where data is obtained from the pulmonary TB population at Hospital X Yogyakarta from 2021-2024 according to the variables studied. Based on the TCM results which are greater than the BTA results, these results indicate a significant difference between the GeneXpert method and the Ziehl-Neelsen method in terms of examination results. The results obtained from the examination using the TCM/GeneXpert and Ziehl-Neelsen methods show a higher detection rate of GeneXpert than Ziehl-Neelsen in identifying TB cases.